Perineural invasion as a predictor of extraprostatic extension of prostate cancer: A systematic review and meta-analysis. (December 2013) - Cozzi, Gabriele; Rocco, Bernardo Maria; Grasso, Angelica; Rosso, Marco; Abed El Rahman, Davide; Oliva, Isabella; Talso, Michele; Costa, Beatrice; Tafa, Ardit; Palumbo, Carlotta; Gadda, Franco; Rocco, Francesco
Abstract A systematic review of the literature was performed to assess the relationship between the presence of perineural invasion (PNI) at prostate biopsy and extraprostatic extension (EPE) of prostate cancer. In August 2012, Medline, Embase, Scopus and Web of Science databases were searched. A "free-text" protocol using the terms "perineural invasion prostate cancer" was applied. Studies published only as abstracts and reports from meetings were not included in this review. In total, 341 records were retrieved from Medline, 507 from Embase, 374 from Scopus and 65 from the Web of Science database. The records were reviewed to identify studies correlating the presence of PNI with that of EPE. A cumulative analysis was conducted using Review Manager software v. 5.1 (Cochrane Collaboration, Oxford, UK). In univariate analysis, PNI showed a statistically significant association with pT3 tumours (p < 0.00001), which could be observed for both pT3a (p < 0.0001) and pT3b (p < 0.0001). In conclusion, the cumulative analysis shows a statistically significant higher incidence of EPE in patients who had PNI at needle biopsy. The main limitation of the analysis was that it was not possible to perform a multivariate analysis. Further attempts to build a nomogram for the prediction of EPE could include the presence of PNI at needle biopsy.